The Opioid System in Rainbow Trout Telencephalon Is Probably Involved in the Hedonic Regulation of Food Intake - Díaz-Rúa, Adrián; Chivite, Mauro; Comesaña, Sara; Conde-Sieira, Marta; Soengas, José L. (Frontiers in Physiology, 2022)
We hypothesize that opioids are involved in the regulation of food intake in fish through homeostatic and hedonic mechanisms. Therefore, we evaluated in rainbow trout (Oncorhynchus mykiss) hypothalamus and telencephalon changes in precursors, endogenous ligands and receptors of the opioid system under different situations aimed to induce changes in the homeostatic (through fasted/fed/refed fish) and hedonic (through feeding fish a control or a palatable high-fat diet) regulation of food intake. No major changes occurred in parameters assessed related with the nutritional condition of fish (fasted/fed/refed), allowing us to suggest that the opioid system seems not to have an important role in the homeostatic regulation of food intake in rainbow trout. The responses observed in telencephalon of rainbow trout fed the palatable high-fat diet included a decrease in mRNA abundance of the opioid precursor penka, in a way similar to that known in mammals, and increased mRNA abundance of the opioid receptors oprd1 and oprk1 supporting a role for telencephalic opioid system in the hedonic regulation of food intake in fish.